Biochar added to a red oxisol benefits the sugar beet seedlings development? - Lima, Stefany Lorrayny; Marimon-Junior, Ben Hur; Tamiozzo, Suelen; Petter, Fabiano André; Marimon, Beatriz Schwantes; Abreu, Mariângela Fernandes (Comunicata Scientiae, 2016)
The objective of this study was to verify the effect of biochar (granulated charcoal) added to an oxisol on the sugar beet seedlings production. The experiment was conducted in the seedlings nursery at the Mato Grosso State University, located at Nova Xavantina municipality, MT, Brazil, during the 2011 crop year. The experiment was carried out in a completely randomized design with five treatments and four repetitions. Different doses of biochar were applied to an oxisol in order to evaluate the seedlings growth and quality, studing the differences between doses of biochar through linear regression. The biochar addition to the oxisol did not promoted growth or quality increase on sugar beet seedlings. All the evaluated treatments presented poor seedlings development and quality, below the optimal level. The addition of low-chemical quality biochar in low fertility soils and with no fertilization is not recommended for sugar beet production during the short seedling production cycle.